Forty-year historical analysis of marine mammal strandings in Texas, from 1980 – 2019 - Piwetz, Sarah; Ronje, Errol I.; Whitehead, Heidi R. (J. Cetacean Res. Manage., 2022)
Long-term trends in marine mammal stranding patterns can provide useful information on basic life history parameters, spatiotemporal distribution, natural and human-related mortality events, and potentially vulnerable populations. Between 1980 and 2019, a total of 5,301 marine mammal strandings were recorded in Texas, USA. In total, 23 species were identified, including 19 odontocete species (toothed whales and dolphins), 3 mysticete species (baleen whales), and 1 sirenian species (manatee). Common bottlenose dolphins (Tursiops truncatus) stranded most frequently (94%). Six unusual mortality events occurred with causes attributed to disease, harmful algal blooms, or unknown etiologies. Common bottlenose dolphin stranding events increased significantly in late winter/early spring, with an early onset in southern Texas, and had a consistent peak in March involving primarily calves and adults. Spatial analyses using kernel density estimation within seven coastal Texas stock management areas, delineated by the National Marine Fisheries Service, identified potential hotspots for common bottlenose dolphin strandings near higher human population density and deep water channels. Peak stranding density estimates in each stock area ranged from 0.32 – 4.6km-2 for presumed bay, sound and estuarine (BSE) stocks and 0.82km-2 for the presumed Western Gulf of Mexico Coastal Stock. Common bottlenose dolphin stranding events were positively male-biased, including a significantly higher number of stranded male fetuses and neonates, and sexual dimorphism was observed in total body length of adults, with significantly greater length in males. For all records where human interaction (HI) could be determined as ‘yes’ or ‘no’, 30% were positive for HI, with the highest proportion of HI events occurring in the central and southern-most BSE stock areas; however, it is unknown how many HI cases contributed to mortality. This longitudinal study provides a comprehensive overview of marine mammal stranding patterns in Texas and serves as a useful resource for stranding investigators and Gulf-wide natural resource managers.